Replication and persistence of simian immunodeficiency virus variants after passage in macaque lymphocytes and established human cell lines. - Rudensey, L M (1993)
In lentivirus infections, there are typically few cells in the host that harbor the provirus. For this reason, molecular clones of human and simian immunodeficiency viruses (HIV and SIV) are generally derived after passage and amplification of the virus in cell culture. To determine whether SIV variants that persist in culture are similar to the variants that predominate in the host, we examined the proviral sequence of the SIV envelope (env) gene before and after cocultivation of lymphocytes from a macaque with AIDS with naive macaque lymphocytes or human cell lines. Many of the predominant variants in the monkey replicated and persisted in macaque lymphocytes and CEMx174 cells in culture, but a more limited population of variants replicated in C8166 cells. Passage of virus, harvested after 4 weeks of coculture, onto naive cells further demonstrated that the majority of proviruses detected by polymerase chain reaction were also viral variants that were expressed and packaged into infectious virions.